Energy and Exergy Analyses of an Innovative Heat Recovery System from the LNG Regasification Process in Green Ships - Roberto Bruno; Vittorio Ferraro; Piofrancesco Barone; Piero Bevilacqua (Clean Technologies, 2024)
Despite being stored at 113 K and at atmospheric pressure, LNG cold potential is not exploited to reduce green ships’ energy needs. An innovative system based on three organic Rankine cycles integrated into the regasification equipment is proposed to produce additional power and recover cooling energy from condensers. A first-law analysis identified ethylene and ethane as suitable working fluids for the first and the second ORC, making freshwater and ice available. Propane, ammonia and propylene could be arbitrarily employed in the third ORC for air conditioning. An environmental analysis that combines exergy efficiency, ecological indices and hazard aspects for the marine environment and ship passengers indicated propylene as safer and more environmentally friendly. Exergy analysis confirmed that more than 20% of the LNG potential can be recovered from every cycle to produce a net clean power of 76 kW, whereas 270 kW can be saved by recovering condensers’ cooling power to satisfy some ship needs. Assuming the sailing mode, a limitation of 162 kg in LNG consumptions was determined, avoiding the emission of 1584 kg of CO2 per day. Marine thermal pollution is reduced by 3.5 times by recovering the working fluids’ condensation heat for the LNG pre-heating.